Pengaruh Kualitas Produk terhadap Kepuasan Konsumen pada UD. Alame Mandailing Rozi Nasution Kecamatan Panyabungan Kabupaten Mandailing Natal - Harisa Umri Nst; Muhlisah Lubis; Sari Fitri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was carried out at UD. Alame Mandailing Rozi Nasution in Kotasiantar, Panyabungan District, Mandailing Natal Regency with the aim of finding out the effect of product quality on consumer satisfaction at UD. Alame Mandailing Rozi Nasution. To achieve the objectives, research was conducted using a sample of 96 people. The research method uses quantitative by describing data using accidental sampling techniques. The research analysis is an analysis of validity and reliability tests, classical assumption tests, simple linear regression tests and hypothesis tests, namely the t test and R square test (with the help of the SPSS Version 21 program). The results of this research indicate that there is an influence of product quality on consumer satisfaction at UD. Alame Mandailing Rozi Nasution. Indicated by a significant value of t 0.000 which is smaller than sig = 0.005 (0.000 < 0.05) the value of R = 0.791 and R Square = 0.626 means that product quality is able to explain the dependent variable or consumer satisfaction of 0.626 × 100% = 62.6% while Another 35.4% is explained by other variables. Based on the research results, it can be concluded that product quality has a positive and significant effect on consumer satisfaction with a value of tcount > ttable (12.535 > 1.664). And product quality has a strong relationship with consumer satisfaction of 0.791.